Analisis Kebijakan Presidential Threshold Dalam Pemilihan Umum 2024 - Rio Putra Simanjuntak; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
General election is the biggest contestation on a national scale which is held every five years. Several facts were found that special election regulations were considered unfair. One of these is the regulation regarding the presidential nomination threshold. The constitution states that political parties can nominate president or vice president when they get 20% of the DPR position or 25% of the national vote. This regulation is considered irrelevant if implemented in the context of simultaneous elections, because the reference for votes is the election that was held four years ago. Practitioners have proposed the Presidential Threshold several times to perform a judicial review to the Constitutional Court. But the Constitutional Court did not accept the request. The Constitutional Court considers the Presidential Threshold as one means to improve the existing presidential system in Indonesia.